2003
DOI: 10.1093/aje/kwg175
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Risk of Newly Diagnosed Asthma in School-age Children

Abstract: To determine the relation between obesity and new-onset asthma among school-age children, the authors examined longitudinal data from 3,792 participants in the Children's Health Study (Southern California) who were asthma-free at enrollment. New cases of physician-diagnosed asthma, height, weight, lung function, and risk factors for asthma were assessed annually at five school visits between 1993 and 1998. Incidence rates were calculated, and proportional hazards regression models were fitted to estimate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
295
3
18

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(335 citation statements)
references
References 50 publications
19
295
3
18
Order By: Relevance
“…Previous studies on overweight and allergy showed conflicting results (Somerville et al, 1984;Schwartz et al, 1990;Gold et al, 1993;Luder et al, 1998;Huang et al, 1999;CastroRodriguez et al, 2001;Chinn & Rona, 2001). Among recent studies, the 5-y prospective Children's Health Study showed that overweight and obese boys, but not girls, were at a higher risk of new-onset asthma (Gilliland et al, 2003); Schachter et al (2003) found that BMI was positively associated with atopy, wheeze and cough but not airway obstruction and airway hyperresponsiveness in 7-to 12-y-old girls, while no association was observed in boys; Romieu et al (2004) reported that a higher BMI was associated with an increased risk of asthma and wheeze in 6-to 16-y-old children and adolescents from the US Third National Health and Nutrition Survey (NHANES III); and To et al (2004) found no association between BMI and asthma among 4-to 11-yold Canadian children. In this study, BMI showed a borderline association with allergy in girls while no association was observed in boys.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies on overweight and allergy showed conflicting results (Somerville et al, 1984;Schwartz et al, 1990;Gold et al, 1993;Luder et al, 1998;Huang et al, 1999;CastroRodriguez et al, 2001;Chinn & Rona, 2001). Among recent studies, the 5-y prospective Children's Health Study showed that overweight and obese boys, but not girls, were at a higher risk of new-onset asthma (Gilliland et al, 2003); Schachter et al (2003) found that BMI was positively associated with atopy, wheeze and cough but not airway obstruction and airway hyperresponsiveness in 7-to 12-y-old girls, while no association was observed in boys; Romieu et al (2004) reported that a higher BMI was associated with an increased risk of asthma and wheeze in 6-to 16-y-old children and adolescents from the US Third National Health and Nutrition Survey (NHANES III); and To et al (2004) found no association between BMI and asthma among 4-to 11-yold Canadian children. In this study, BMI showed a borderline association with allergy in girls while no association was observed in boys.…”
Section: Discussionmentioning
confidence: 98%
“…CastroRodriguez et al (2001) reported that girls who became overweight or obese between 6 and 11 y of age were more likely to develop new asthma symptoms, but no such association was observed in boys. In a 5-y longitudinal study, Gilliland et al (2003) reported that being overweight increased the risk of new-onset asthma in boys but not in girls.…”
Section: Introductionmentioning
confidence: 99%
“…Children in the 4 th , 7 th and 10 th grades were recruited in 1993 and 1996 and followed through high school graduation. Associations of asthma with housing characteristics, obesity, air pollution, family history and exercise have been previously described (Gauderman, Avol, Lurmann, Kuenzli, Gilliland, Peters et al, 2005;Gilliland, Berhane, Islam, McConnell, Gauderman, Gilliland et al, 2003;Kunzli, McConnell, Bates, Bastain, Hricko, Lurmann et al, 2003;London, James Gauderman, Avol, Rappaport, & Peters, 2001;McConnell, Berhane, Gilliland, Islam, Gauderman, London et al, 2002a;McConnell, Berhane, Gilliland et al, 2002b;McConnell, Berhane, Yao, Jerrett, Lurmann, Gilliland et al, 2006). A detailed description of the selection of communities, subject recruitment, and survey methods to assess demographic, household, activity, and baseline medical characteristics has also been reported (Peters, Avol, Navidi, London, Gauderman, Lurmann et al, 1999).…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Socioeconomic position and other demographic, medical and home environmental exposures have been examined in the CHS with respect to childhood asthma (Gauderman, Avol, Lurmann et al, 2005;Gilliland, Berhane, Islam et al, 2003;Peters, Avol, Navidi et al, 1999). Variables of interest here include age of the child (centered on 10 years of age), race/ethnicity, gender, height, age-and sex-adjusted body mass index below the 10 th percentile or in the 90 th percentile, cohort group (defined by year and subject's grade at enrollment: 1993 in 4 th , 7 th or 10 th grade or 1996 in 4 th grade), current vitamin use, hay fever symptoms in the last 12 months, current medical insurance coverage and parental history of asthma.…”
Section: Individual Variablesmentioning
confidence: 99%
“…4 A growing body of literature has reported a relationship between asthma and obesity among adults. 5,6 Studies conducted among children, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] however, have produced conflicting results thus far, and further elucidation is necessary of how an association between asthma and body mass index (BMI) may differ by population characteristics, such as age, gender, and race/ethnicity. In addition, many studies among children have failed to assess the potential effect across the full range of BMI percentiles, including those who are underweight.…”
Section: Introductionmentioning
confidence: 99%